Flow characteristics and drag reduction of tandem Serie-parallel circular cylinders: acombined numerical and experimental study - W. Rauf; M. Rifal; R. Pido; R.H. Boli; N. Bumulo (Universitas Mataram, 2026)
This study investigates the fluid flow characteristics and aerodynamic forces acting on three circular cylinders arranged in a tandem serial–parallel configuration using a combination of numerical simulations and experimental measurements. The spacing ratio between cylinders (N/D) was varied from 0.1 to 1.1, while the Reynolds number ranged from 5,029.6 to 21,124.4. The numerical analysis was conducted using Computational Fluid Dynamics (CFD) to evaluate the flow structure and drag coefficient (Cd), and the results were subsequently validated through experimental testing in a subsonic wind tunnel. The findings indicate that both the inter-cylinder spacing and the Reynolds number have a significant influence on wake structure, pressure distribution, and drag magnitude. At small N/D ratios, strong wake interactions between the cylinders generate extensive recirculation zones, low rear pressure, and high drag coefficients. As the N/D ratio increases, wake interference weakens, the flow becomes more orderly and symmetric, and the pressure distribution becomes more uniform, leading to a substantial reduction in drag. A consistent decrease in Cd with increasing Reynolds number is also observed for all configurations. The close agreement between numerical and experimental results demonstrates that the CFD approach accurately captures the flow behavior and aerodynamic forces. These findings provide valuable insights for optimizing tandem cylinder geometries in engineering applications, particularly for drag reduction and the enhancement of aerodynamic efficiency.